Bud-break promoters for the improvement of the budburst of pecan cultivars - Rosa Júnior, Horacy Fagundes da (2022)
The objective of this work was to evaluate the effect of different bud-breaking substances on the budburst of the Barton, Desirable, and Jackson pecan (Carya illinoinensis) cultivars. The experimental design was a randomized complete block with four replicates. The treatments consisted of spraying different rates of commercial bud-break promoters on the trees of these cultivars, in order to induce budburst. The budburst percentage of axillary buds and the budburst heterogeneity index (BHI) were evaluated. Regardless of the used rate, the application of the hydrogen cyanamide product improved the budburst of the tested cultivars and reduced the BHI. In addition, water soluble N + Ca at 6% and water soluble N + organic C soluble in water at 7% significantly improve the budburst and reduce the BHI of the evaluated cultivars, being, therefore, potential alternatives to replace hydrogen cyanamide.